Frequency of genetic polymorphism for adrenergic receptor beta and cytochrome p450 2D6 enzyme, and effects on tolerability of beta-blocker therapy in heart failure with reduced ejection fraction patients: The Beta GenTURK study - Mehdi Zoghi; Hakki Kaya; Yuksel Cavusoglu; Enbiya Aksakal; Serafettin Demir; Ceyhun Yucel; Hasim Mutlu; Oktay Ergene; Mehmet Birhan Yilmaz; On Behalf Of The Beta Genturk Study (KARE Publishing, 2016)
Objective: The present objective was to determine frequency of Arginine389Glycine (Arg389Gly) and Cytochrome p450 2D6*10 (Cyp2D6*10) polymorphism in cases of heart failure-reduced ejection fraction (HFREF), and to evaluate the influence of the polymorphisms in response to beta-blocker (BB) therapy. Methods: A total of 206 HFREF patients and 90 healthy controls were prospectively enrolled. Genotypes for Arg389Gly and Cyp2D6*10 polymorphisms of the healthy controls and 162 of the 206 heart failure (HF) patients were measured, identified by polymerase-chain-reaction- and restriction-fragment-length-polymorphism analysis. HFREF patients and healthy controls were compared regarding Arg389Gly polymorphism. The HFREF patients were separated into 2 subgroups based on achievement of maximal target dose (MTD) of BB. Results: When comparing frequency of genotype distribution for Arg389Gly polymorphism in HFREF patients to the healthy controls, a statistically significant association was observed with CC genotype and Glisin-Glisin (GG) genotype (p<0.001, odds ratio [OR]=16, confidence interval [CI]: 3.8-67.9 and p<0.001, OR=0.3, CI: 0.2-0.6). Frequency of genotypes for Arg389Gly and Cyp2D6*10 polymorphism were similar in patients who could or could not achieve BB MTD (p=0.13 and p=0.60, respectively). Conclusion: The frequency of Arg389Gly polymorphism in patients with HFREF in the present Turkish population differed from that of the healthy controls. However, neither Arg389Gly polymorphism nor Cyp2D6*10 polymorphism was associated with dose tolerability of BB therapy.